The Effect of Motivational Entrepreneurship on Business Performance of SMEs Moderated by Process Innovation. - Machmud, Senen (Archives of Business Research, 2017)
This study aims to determine the effect of motivational entrepreneurship to the innovation process and the performance of entrepreneurs. The population in this study are two centers of business in Bandung: Sentra Rajut Binongjati (the knitting business center) and Sentra Kaos Suci (the t-shirts business center). The samples in this study are 154 SMEs owners. Data analysis techniques use Partial Least Square - Structural Equation Modeling. The results show that motivational entrepreneurship which consists of achievement motivation, risk propensity, and self-efficacy have significant effects either on the innovation process and the business performance. It indicates that the achievement motivation, willingness to take risks and self-efficacy can generate innovation processes and improve business performance. Keywords: Achievement motivation; Risk propensity; Self-Efficacy; Innovation; Performance; SME.